Pengukuran Usability dan Respon Emosional Pengguna pada Aplikasi Cyber Counseling untuk Mengidentifikasi Masalah Interaksi - Endang Fatmawati; Amri Amri; Gogor Christmass Setyawan; Dimas Sasongko (STMIK Budi Darma, 2022)
The Cyber Counseling mobile application allows users with different backgrounds to visit, so evaluating the application's user interface is necessary. Usability has attributes to determine the user interface that users can use easily to achieve a goal. Emotions are subjective and conscious events illustrated primarily through psychophysiological expressions and biological reactions. Moreover, emotion is a complex feeling that affects the user's performance. In this study, usability testing uses a System Usability Scale questionnaire, and emotional responses will be measured by measuring affective reactions using the Self-assessment Manikin questionnaire. The results of usability testing using the System Usability Scale questionnaire show that the perspective of test participants about the Cyber Counseling mobile application is to have acceptability ranges in the acceptable category, have a grade scale with category C, and have an adjective rating in the good category. The results of measuring emotional responses using the Self-assessment Manikin questionnaire on the pleasure indicator have a happy emotional response, the arousal indicator has an enthusiastic emotional response, and the dominance indicator has an emotional response capable of operating the Cyber Counseling mobile application.This research has a contribution that by combining the usability method and measuring the user's emotional response, it not only provides information on the ease of using the application but also provides information about the affective reaction of the user when using the application